Strategi Pengelolaan Ziswaf untuk Meningkatkan Perekonomian Masyarakat di Kabupaten Rupat Riau (Studi Kasus Baznas Kabupaten Rupat Riau) - Ramlan Indra Jaya (Jurnal Al-Tatwir, 2020)
Indonesia is a country with the largest Muslim population in the world, it can be seen from 85.1% of the Indonesian population who are Muslim. This research was designed with a qualitative approach. To obtain facts from the existing symptoms and seek factual information. A qualitative approach is used to describe complex realities in the field and to obtain the accuracy of facts in the field with the right interpretation. This research was carried out in the Islamic Economics Festival (FESyar) (7/10) entitled Empowerment of Zakat in the Era of Society 5.0. In a publication published by BAZNAS, zakat is a tool to control the increase in GDP and reduce economic inequality. The 2019 data shows a slowdown in economic growth with a decline in the level of public consumption. This continues in 2020 with the addition of the pandemic and recession. This is evidenced by the significant increase in Indonesian society carried out by BAZNAZ in the withdrawal of Zakat, Infaq and Alms funds in 2020. During the pandemic, the community's economic income was reduced. Due to the impact of the COVID-19 pandemic. But in reality the funds went up. One of the factors that make this increase happen is because there are. A persuasive da'wah approach or da'wah that directly presents a phenomenon. Poverty or the impact of a pandemic that makes the poor poorer. With this fact makes the community mutual help each other. In micro and macro economic policies, it has fulfilled the elements that there is inflation from the impact of the pandemic and there is a significant increase in the ZISWAF funds.